Discretionary Authority of Government Officials in State Administrative Law: Between Effectiveness and Accountability - Agus Wardhono (Journal of Creative Power and Ambition (JCPA), 2026)
Discretion is an important instrument in governance to ensure the effectiveness of public services, particularly in situations of legal vacuum, unclear norms, or urgent situations. However, the use of discretion by government officials also has the potential for abuse, which can undermine the principles of accountability and legal certainty. This article aims to analyze the concept of discretion in state administrative law and examine the legal limits of its use to ensure alignment with the principles of the rule of law and good governance. This study uses normative legal research methods with legal, conceptual, and doctrinal approaches. The results show that discretion can only be justified if it is implemented based on legitimate government objectives, based on general principles of good governance, and accompanied by clear accountability mechanisms. Strengthening the accountability aspect in the use of discretion is a key prerequisite for preventing abuse of authority and ensuring effective governance. Thus, the regulation and oversight of government officials' discretion contribute to strengthening effective, accountable, and transparent public institutions.